Nuclear and extended families to risk of early childhood caries - Dr Abhinav Singh; Dr Bharathi M Purohit; Dr Abhishek Purohit; Mrs Nilima (Elsevier, 2023)
Aim or Purpose: This study aims to assess independent contributions of nuclear and extended families through direct and indirect pathways towards risk of early childhood caries among 5 years old children from low socio-economic status in Central India. Materials and Methods: A two-stage sampling design was used to randomly select a total of 313 school children. The American Association of Pediatric Dentistry defined criterion was used for diagnosis of early childhood caries (ECC) and severe early childhood caries (S-ECC). It was hypothesized that type of family would impact ECC and S-ECC directly and indirectly through acting on individual level variables like frequency of cleaning teeth, dietary patterns, and utilization of dental services. Generalized structural equation modelling (GSEM) was adopted to examine the relationship between a set of exogenous variables. Path coefficients along with the standard error with 95% confidence interval were reported. Results: A total of 186 (59.4%) and 47 (15%) children had ECC and SECC. Nuclear families, higher frequency of between meal sugar consumption, and lower utilization of dental care were significantly associated with ECC with odds ratio of 2.43, 2.78 and 8.65 respectively (p< 0.001). Nuclear families were also significantly associated with SECC. Type of family had significant direct (p< 0.001) and indirect (p< 0.05) effects via three or more than three times sugar consumption and lower utilization of dental services on ECC. Conclusions: Nuclear families were significantly associated with ECC and SECC among the children. Practicing dentists need to understand the influence of type of family and the associated pathway to tackle and reduce the burden of ECC.